Implementation of Positive Self‑Talk, Interpersonal Communication, and Activity Involvement to Manage Hallucinations in Patients with Schizophrenia - Amalia, Shela Putri; Rismawan, Wawan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Auditory perceptual disturbances in the form of hallucinations are commonly experienced by patients with schizophrenia and may interfere with daily functioning if not properly managed. One nursing intervention to help patients control hallucinations is the implementation of structured intervention strategies (SP I–IV). This study aimed to describe the application of these strategies in improving patients’ ability to control auditory hallucinations. This study was a case report conducted on four patients with schizophrenia who experienced auditory hallucinations and were treated in the Perkutut Ward of the West Java Provincial Psychiatric Hospital. Data were collected through interviews, observation, and nursing care documentation. The data were analyzed using a qualitative descriptive approach. The results showed that the structured and routine implementation of the intervention strategies reduced the frequency and intensity of auditory hallucinations and improved patients’ ability and independence in controlling them. It can be concluded that the implementation strategies are effective as part of psychiatric nursing care. Therefore, these strategies are recommended to be applied consistently in nursing practice for patients with auditory hallucinations.Keywords: auditory hallucinations; schizophrenia; nursing implementation strategies; symptom management